Celovita prenova naselja Štanjel - Deu, Živa (Urbani izziv, 2005)
In the Karst region the settlements Štanjel and Kobdilj form a uniform settlement structure, which is visually marked by old Štanjel, a unique medieval settlement with primeval settlement tradition. Because of a myriad of reasons, not needing mentioning, in the decades after the Second World War the identity of this exceptional cultural landscape was gradually eroded by spatial, urbanistic and architectural development of the two settlements. In these processes of erosion of distinguishable characteristics of the cultural landscape, as important values in the formation of quality living, dilapidation of old Štanjel, a cultural value of national and European significance, was most evident. The first more or less unnoticed turn in the settlements development, which began in the 80s of the last century with the partial renewal of the Štanjel castle, was followed after independence with the adopted Common development programme of Karst municipalities and preparation of normative documents for the settlement Štanjel. All normative documents, especially the Municipal location plan for spatial management of Štanjel - old core, described in the article, were done in compliance with principles of sustainable development and new internatiobal directions concerning comprehensive preservation of built heritage, as well as active public participation.
Keywords: arhitekturna dediščina; karst; Kras; prenova; revitalizacija; stavbna dediščina; Štanjel; varstvo kulturne dediščine